1999
DOI: 10.1097/00006123-199905000-00134
|View full text |Cite
|
Sign up to set email alerts
|

The Safety of OP-1 for Lumbar Fusion with Decompression - a Canine Study

Abstract: Recombinant human OP-1 is effective at promoting fusion in a canine dorsolateral lumbar spine fusion model. However, bone growth can occur over exposed, decompressed dura, and it can form in the subdural and subarachnoid spaces. The use of OP-1 as an adjunct to spinal fusion appears to have merit, but its use must be carefully controlled to avoid unwanted bone formation and subsequent neural compression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(39 citation statements)
references
References 16 publications
0
39
0
Order By: Relevance
“…Paramore et al implanted BMP-7 into the epidural space of dogs after laminectomy and posterolateral fusion. Animals demonstrated bone formation adjacent to their spinal cords causing mild spinal cord compression (Paramore et al 1999). Novel carriers need to contain the BMP, prevent ectopic and heterotopic bone formation and utilize lower, safe and costeffective dosages.…”
Section: Dose and Concentrationmentioning
confidence: 99%
“…Paramore et al implanted BMP-7 into the epidural space of dogs after laminectomy and posterolateral fusion. Animals demonstrated bone formation adjacent to their spinal cords causing mild spinal cord compression (Paramore et al 1999). Novel carriers need to contain the BMP, prevent ectopic and heterotopic bone formation and utilize lower, safe and costeffective dosages.…”
Section: Dose and Concentrationmentioning
confidence: 99%
“…In another canine model of dural perforation, Paramore, et al, 48 studied the safety of rhBMP-7 (rhOP-1) use. After laminectomy, the dura was opened to simulate an intraoperative dural rent.…”
Section: Animal Models Of Bmp Safetymentioning
confidence: 99%
“…Although placement of rhBMP-2 5 or bovine whole BMP extract 13 in the posterolateral location in an animal laminectomy model did not result in any significant encroachment of bone into the laminectomy defect, undesired bone formation was seen directly over the laminectomy defect with placement of rhBMP-2 36 or rhBMP-7. 48 Other models have induced spinal stenosis by direct implantation of BMP over the ligamentum flavum. 37,40 In the setting of dural laceration in animal models, significant intradural bone formation and calcification of the spinal cord was seen with rhBMP-7 48 , but not with rhBMP-2, 36 although the studies were not of similar design.…”
Section: 41mentioning
confidence: 99%
See 1 more Smart Citation
“…Further efforts led to cloning of BMP-2 and BMP-7 (OP-1), members of the transforming growth factor-beta (TGF-beta) superfamily, and expression of recombinant human forms of these proteins (11,12). Both rhBMP-2 and rhOP-1 demonstrated efficacy in inducing bone formation in preclinical animal studies, which has spurred clinical investigation of their efficacy as bone graft substitute (13)(14)(15)(16). Moreover, other investigators have suggested that BMPs, including OP-1, may show promise in promoting fusion in patients with high-risk adverse medical conditions (17).…”
mentioning
confidence: 99%